2021
DOI: 10.3390/su13041614
|View full text |Cite
|
Sign up to set email alerts
|

“Not as Safe as I Believed”: Differences in Perceived and Self-Reported Cycling Behavior between Riders and Non-Riders

Abstract: Cycling behavior remains a key issue for explaining several traffic causalities occurring every day. However, recent studies have shown how the assessment of the own safety-related behaviors on the road may substantially differ from how third parties assess them. Thus, the aim of this study was to evaluate the differences between cyclists’ self-reported behavior and the proxy-reported behavior that other (non-cyclist) road users perceive from bike riders. For this purpose, this study used data from two samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…Maybe not everyone will honestly report this type of dangerous behavior. The self-reported and the external-rated behavior greatly differ ( Useche et al., 2021 ). Therefore, we can explore whether the self-perception of riding electric bicycles will be different from that of other users in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Maybe not everyone will honestly report this type of dangerous behavior. The self-reported and the external-rated behavior greatly differ ( Useche et al., 2021 ). Therefore, we can explore whether the self-perception of riding electric bicycles will be different from that of other users in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study on pedestrians and drivers’ perceptions of common traffic behaviors point out that there are significant differences in regard to the way they perceive other road users’ behavior. Previous studies have also addressed certain discrepancies on the assessment of the risky roadand protective behaviors performed by third parties, showing that—overall—road users tend to perceive their road behaviors as “safer” than the ones assessed in other users (Useche et al, 2021). Concretely, the results of this research have depicted how pedestrians do not hold a considerably positive opinion of drivers’ behavior; as a matter of fact, significant differences are spotted in those behaviors that can be considered unsafe.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to consider the possibility of having made conclusions over potentially biased information as a first key limitation. Even though the anonymity of the study and its rigorously scientific character were emphasized, recent studies have sometimes shown huge discrepancies between the self-reported and the actual behavior of road users (Drupsteen et al, 2013; Useche et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, this pattern shows a certain level of concordance with the one found by studies that compare perceptions from different road users regarding risky or safety behaviors of single types of road users. In this type of studies, self-reported road behaviors are largely positive when road users grade their own behavior, while external raters' assessment tends to be comparatively critical (Wood et al, 2009;Arai et al, 2010;Li et al, 2016;Duarte and Mouro, 2019;Useche et al, 2021a).…”
Section: Ecuadormentioning
confidence: 99%